Collaborative Governance in Fostering Functional Positions of Policy Analysts in Indonesia - Muthmainah, Erfi; Prasetyo, Antonius Galih (KnE Social Sciences, 2025)
The policy analyst is a functional position within government institutions established by the National Institute of Public Administration (NIPA) to improve the quality of public policy. As the agency responsible for fostering this role, NIPA encounters significant complexities and challenges prompting the need for collaboration with various parties. In this context, collaborative governance emerges as the most appropriate governance model. This study explores how NIPA implements collaborative governance in the development and support of policy analysts. Using a qualitative research approach, the study combines interviews with policymakers and a literature review. The findings reveal that NIPA’s collaboration efforts are driven by multiple enabling factors. Furthermore, the three main components of collaborative governance–principled engagement, shared motivation, and capacity for joint action–have also been reflected in the collaboration process. The study concludes that NIPA’s approach to fostering policy analysts effectively aligns with the collaborative governance framework. Practically, this research demonstrates how collaborative governance can be applied to the development of functional positions within government. It contributes to the broader discourse on collaborative governance by highlighting its application in an underexplored area: the fostering of government functional roles.